Nanotechnologies for water environment applications - Zhang, Tian C. (American Society of Civil Engineers : EWRI, 2009)
Sponsored by the Nanotechnology Task Committee of the Environmental Council of the Environmental and Water Resources Institute of ASCE. This report provides the current status of synthesis and characterization of nanomaterials, as well as the environmental effects of nanotechnology. Nanotechnology, the engine of the next Industrial Revolution, represents the new wave of research for chemical and industrial innovation. Any new technology or compound, however, comes with the threat of harm to humans and natural ecosystems. Research into the environmental effects--as well as the ethical, legal, and social implications--of nanotechnologies and nanoproducts has never been more important. Topics include: the major applications of nanotechnologies in various water environments; issues related to the fate and transport of nanomaterials in aquatic environments; engineered nanomaterials as emerging contaminants in water; and the environmental risks and related management of nanomaterials. Extensive up-to-date references are provided. This book is useful to undergraduate and graduate students in engineering and practicing engineers, as well as educators, scientists, government officials, policymakers, and industrial process managers.
Keywords: Water -- Purification -- Technological innovations.; Water -- Pollution -- Prevention.; Nanotechnology.; Nanostructured materials -- Environmental aspects.; Nanotechnology -- Environmental aspects.; Water -- Purification.; elektronické knihy; electronic books